A composition for Ganoderma disease in plants - Musa, Mohd. Hanafi; Abu Seman, Idris (2012)
A composition comprising organic fertilizer granule containing silicon dioxide (SiO2) prepared using organic materials from oil palm mill wastes and silicon dioxide (SiO2) powder. This composition is used for oil palm growth and controlling of Ganoderma disease in nursery, immature, and mature stages. This formulation may also be used for other plants affected by Ganoderma disease.